ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIK SISWA SMP KELAS VII PADA MATERI SEGITIGA DAN SEGIEMPAT - Adi Sulistio Pratama; Marchasan Lexbin Elvi Judah Riajanto (IKIP Siliwangi, 2021)
Students' mathematical communication skills need to be known given that this ability is very necessary for students. So, this study focuses on knowing these abilities in triangular and quadrilateral material. The subjects were 35 students of class VIID SMP PGRI 384 Rendeh. The form of data retrieval is by giving 5 written test items. The data obtained were given a score and then grouped according to the category of mathematical communication skills. The data analysis technique uses scoring calculations with categorization based on the percentage of student scores. Based on the results of the analysis, the mean value of all instruments obtained for the indicators connecting real objects and diagrams into real life is 69% and 80%, respectively. Explain situation ideas and mathematical relations verbally with real objects, pictures, graphics and algebra, namely 72%. Expressing everyday events in language or mathematical symbols, namely 65%. Making conjectures, formulating definitions, generalizations, and making arguments 73%. So that if it is totaled and averaged it reaches 72%. So the mathematical communication skills of class VIID SMP PGRI 384 Rendeh are high.